. Predictive Value Of Serological Markers And Immune Indicators Combined With Early Warning Scoring System For Prognosis In Pediatric Acute Respiratory Infections: Respiratory Infection Prognosis Prediction by AVPU Score + Serological Markers - Zhu, Yanyan (Journal of Medical Biochemistry, 2025)
Objective: it was to evaluate the combined utility of alertness-vigilance-pain-unresponsiveness (AVPU) scoring and serological factors in predicting outcomes for children with acute respiratory infections (ARIs) in the emergency department. Materials and Methods: 100 children with ARIs were categorized based on their outcomes into good prognosis group (GPG, n=79) and poor prognosis group (PPG, n=21). AVPU scores, serum inflammatory markers (SIMs), and immune indicators (levels of immunoglobulins IgA, IgG, IgM, and the counts of CD3+, CD4+, CD8+, CD19+, and NK cells) were compared at admission between groups. Pearson correlation analysis was employed to examine the relationship between AVPU scores and SIMs, and the plotted receiver operating characteristic (ROC) curves assessed diagnostic performance. Results: at admission, GPG had markedly inferior AVPU scores and SIMs (WBC, CRP, IL-6, and PCT) to the PPG (P<0.05). AVPU scores were not notably correlated with SIMs (P>0.05). Among individual indicators, AVPU scoring demonstrated relatively high sensitivity (Sen) and specificity (Spe) for predicting poor prognosis (P<0.05). Combined detection of AVPU scores and serological factors greatly enhanced both Sen and Spe for predicting poor prognosis versus individual indicators (P<0.05). Conclusion: AVPU scoring alone shows high Sen and Spe for prognosis assessment. The combined use of AVPU scoring and SIMs significantly enhances the Sen and Spe of prognostic evaluation, demonstrating its clinical value.